Intra-Household Insurance and the Intergenerational Transmission of Income Risk - Francesco Agostinelli; Domenico Ferraro; Xincheng Qiu; Giuseppe Sorrenti (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper studies the mechanisms and the extent to which parental wage risk passes through to children's skill development. Through a quantitative dynamic labor supply model in which two parents choose whether to work short or long hours or not work at all, time spent with children, and child-related expenditures, we find that income risk impacts skill accumulation, permanently lowering children's skill levels. To the extent that making up for cognitive skill losses during childhood is hard—as available evidence suggests—uninsurable income risk can negatively impact the labor market prospects of future generations.
Keywords: D10; J13; J22; 330; wage risk; household labor supply; child development; social insurance